A rapid real-time PCR method to differentiate between mottled skate (Beringraja pulchra) and other skate and ray species. (30th July 2018) - Kim, Mi-Ra; Kwon, Kisung; Jung, Yoo-Kyung; Kang, Tae Sun
Highlights: Sensitive Beringraja pulchra -specific and skate-universal primer sets were designed. Accurate and reliable qPCR method was developed for identification of skate species. Ultra-fast qPCR assay within 30 min was also developed for on-site identification. Abstract: Skates and rays are commercially important fish in South Korea, and among them, Beringraja pulchra has the highest economic value. However, the similar morphological traits among skates and rays are often exploited for seafood fraud. Here, we designed both Beringraja pulchra -specific and skate-universal primer sets, capable of detecting short sequences in the cytochrome oxidase subunit I gene, and developed highly sensitive and reliable quantitative real-time PCR (qPCR) assays to differentiate between Beringraja pulchra and other skate and ray species. AΔCq method based on differences in the amplification efficiency was developed, validated, and then used to confirm the presence of Beringraja pulchra in twenty-six commercial skate products. The averageΔCq value obtained for other skate species (18.94 ± 3.46) was significantly higher than that of Beringraja pulchra (1.18 ± 0.15). For on-site applications, we developed an ultra-fast qPCR assay, allowing for completion of the entire analytical procedure within 30 min.